2012
DOI: 10.1039/c2ee21679e
|View full text |Cite
|
Sign up to set email alerts
|

Top ten fundamental challenges of biomass pyrolysis for biofuels

Abstract: Pyrolytic biofuels have technical advantages over conventional biological conversion processes since the entire plant can be used as the feedstock (rather than only simple sugars) and the conversion process occurs in only a few seconds (rather than hours or days). Despite decades of study, the fundamental science of biomass pyrolysis is still lacking and detailed models capable of describing the chemistry and transport in real-world reactors is unavailable. Developing these descriptions is a challenge because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
412
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(420 citation statements)
references
References 86 publications
4
412
0
4
Order By: Relevance
“…Aznar et al [32] and Andre et al [35] also identified an increase in tar yield with an increase in biomass content of the feedstock, suggesting that synergetic effect during coal and biomass co-gasification might be highly dependent on biomass type as well as gasification conditions. One of the challenges emphasized by Mettler et al [138] in their reviews of fundamental challenges of biomass pyrolysis for biofuels is the difficulty still encountered by researchers to identify and characterize nascent liquid intermediaries evolved during biomass pyrolysis. Therefore, the pertinence of these intermediates during co-conversion with coal is unknown.…”
Section: Effects Of Co-conversion Of Coal and Biomass/waste On Tar Rementioning
confidence: 99%
“…Aznar et al [32] and Andre et al [35] also identified an increase in tar yield with an increase in biomass content of the feedstock, suggesting that synergetic effect during coal and biomass co-gasification might be highly dependent on biomass type as well as gasification conditions. One of the challenges emphasized by Mettler et al [138] in their reviews of fundamental challenges of biomass pyrolysis for biofuels is the difficulty still encountered by researchers to identify and characterize nascent liquid intermediaries evolved during biomass pyrolysis. Therefore, the pertinence of these intermediates during co-conversion with coal is unknown.…”
Section: Effects Of Co-conversion Of Coal and Biomass/waste On Tar Rementioning
confidence: 99%
“…3 In particular, a low-temperature non-enzymatic pathway has been developed to produce 2-methylfuran (2MF) and 2,5-dimethylfuran (DMF) from cellulose. DMF is a promising biofuel since it has an energy content 2,4,5 (29.6 kJ cm -3 at 298 K) similar to that of gasoline (≅ 32 kJ cm -3 at 298 K) and significantly greater than that of ethanol (21.2 kJ cm -3 at 298 K).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that there will be other fuels derived from lignocellulosic biomass beyond 2MF and DMF. 3 (1)…”
Section: Introductionmentioning
confidence: 99%
“…In raw biomass, groups of adjacent cells form a multicellular porous structure comprised of smaller (lumen) and larger (parenchyma) cavities making escape of intermediate products of pyrolysis through cavities easier [43].…”
Section: 3mentioning
confidence: 99%